2011
DOI: 10.1007/s12562-011-0437-5
|View full text |Cite
|
Sign up to set email alerts
|

Variations in cryptic assemblages in coral-rubble interstices at a reef slope in Ishigaki Island, Japan

Abstract: The interstices of coral rubble provide a good refuge for cryptic small crustaceans and molluscs, which are important prey items for reef fishes. In this study, we focused on the assemblage composition of cryptic mobile species along the depth gradient at an outer reef slope. Traps with coral rubble (22 9 18 9 6 cm) were set at three sites at different depths, and mobile animals that colonized the traps were sorted. In total, 117 species of larger animals (mainly Decapoda and Gastropoda) were recorded: 71 spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Differences in cryptofauna communities along depth profiles have been reported previously. For example, densities of the squat lobster, Galathea mauritiana (Decapoda: Galatheidae), which can be the most abundant species in shallow‐water (3 m) cryptic communities, decreased with depth to zero at 22 m in reefs of Ishigaki Island, Japan (Takada et al, 2008, 2012). We did not find galatheids in high numbers but their density in shallow rubble patches here was twice that of deep patches.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in cryptofauna communities along depth profiles have been reported previously. For example, densities of the squat lobster, Galathea mauritiana (Decapoda: Galatheidae), which can be the most abundant species in shallow‐water (3 m) cryptic communities, decreased with depth to zero at 22 m in reefs of Ishigaki Island, Japan (Takada et al, 2008, 2012). We did not find galatheids in high numbers but their density in shallow rubble patches here was twice that of deep patches.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaidaceans are sometimes reported in ecological surveys documenting faunal assemblages. In Japan, a few such surveys have included this crustacean, including the four studies (Mukai 1971;Kito 1975;Matsumasa and Kurihara 1988;Nakaoka et al 2001) mentioned above under 'Phenology'; studies on temporal and spatial variation in community structure and the effects of environmental factors in a seagrass ecosystem (Yamada et al 2007(Yamada et al , 2014; studies of differences in the faunal assemblage among habitats (seagrass bed-coral surface-sandy bottom) or along a depth gradient (Nakamura and Sano 2005;Nakamura et al 2012;Takada et al 2012); and a study comparing tanaidacean diversity and abundance among deep-sea sampling sites (Błażewicz-Paszkowycz et al 2015a). By using experimental substrata in a brackish lagoon, examined the effects of secondary substratum type on small crustacean assemblages, focusing on three amphipods and a tanaidid, Sinelobus stanfordi, and found that the type of secondary substratum directly determined the dominant species.…”
Section: Ecological Surveysmentioning
confidence: 99%
“…For emergent fauna, migration from the benthos at night results in a reshuffling of populations while predation risk is reduced (Alldredge & King, 1977 ; Takada et al, 2016 ), as biomass and productivity of nocturnal fishes is lower than diurnal species (Collins et al, 2022 ). Yet, for many rubble‐dwelling taxa, movement is likely to be highly constrained within the rubble cryptobenthos where they remain inconspicuous to top‐down predators (Takada et al, 2016 ), shaped by water depth (Takada et al, 2008 , 2012 ), rubble morphology (Biondi et al, 2020 ), and the prevalence of sessile taxa, such as algae and sponges (Enochs, 2012 ; Gonzalez‐Gomez et al, 2018 ; Kramer et al, 2012 ; Logan et al, 2008 ; Tews et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%